2015
DOI: 10.1366/14-07720
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared (NIR) Spectroscopy of Synthetic Hydroxyapatites and Human Dental Tissues

Abstract: Near-infrared spectroscopy (NIR) was used to analyze synthetic hydroxyapatite calcined at various temperatures, synthetic carbonated hydroxyapatite, and human hard dental tissues (enamel and dentin). The NIR bands of those materials in the combination, first-overtone, and second-overtone spectral regions were assigned and evaluated for structural characterization. They were attributed to adsorbed and structural water, structural hydroxyl (OH) groups and surface P-OH groups. The NIR spectral features were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 65 publications
1
71
0
2
Order By: Relevance
“…Mid-infrared spectral absorbances from apatite and other calcium phosphates arise primarily from the phosphate component, and the contour and frequencies of the phosphate absorbances are spectral fingerprints for the type and amount of mineral present in tissue [34]. In contrast, there is no phosphate (PO 4 ) absorbance in the NIR spectral region[64]. However, there are small absorbances from P-OH moities of hydroxyapatite, and from water on the surface or bound to the mineral phase[64].…”
Section: 0 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mid-infrared spectral absorbances from apatite and other calcium phosphates arise primarily from the phosphate component, and the contour and frequencies of the phosphate absorbances are spectral fingerprints for the type and amount of mineral present in tissue [34]. In contrast, there is no phosphate (PO 4 ) absorbance in the NIR spectral region[64]. However, there are small absorbances from P-OH moities of hydroxyapatite, and from water on the surface or bound to the mineral phase[64].…”
Section: 0 Discussionmentioning
confidence: 99%
“…In contrast, there is no phosphate (PO 4 ) absorbance in the NIR spectral region[64]. However, there are small absorbances from P-OH moities of hydroxyapatite, and from water on the surface or bound to the mineral phase[64]. Understanding these absorbances could indeed be helpful for investigation of bone quality, but the challenge of confirming these low-intensity absorbances in intact bone requires a separate thorough investigation.…”
Section: 0 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of water, even after drying, can also be attributed to the high hydrophilicity of the calcium phosphate crystals formed on the surfaces of the nanocomposites. From the NIR spectra of synthetic apatites, Kolmas et al observed the behavior of the adsorbed water in calcium phosphate crystals and verified that it could be present in different ways: (1) as structural water contained in the internal volume of the crystalline lattice; (2) as water adsorbed by Ca + cations or by hydrogen bonds in the P‐OH groups present on the surfaces of the crystal, or (3) as free surface water.…”
Section: Resultsmentioning
confidence: 99%